Vibrotactile auricular vagus nerve stimulation alters limbic system connectivity in humans: A pilot study - Kara M. Donovan; Joshua D. Adams; Ki Yun Park; Phillip Demarest; Gansheng Tan; Jon T. Willie; Peter Brunner; Jenna L. Gorlewicz; Eric C. Leuthardt (PLoS ONE, 2025)
Vibration offers a potential alternative modality for transcutaneous auricular vagus nerve stimulation (taVNS). However, mechanisms of action are not well-defined. The goal of this pilot study was to evaluate the potential of vibrotactile stimulation of the outer ear as a method for activating central brain regions similarly to established vagal nerve stimulation methods. Seven patients with intractable epilepsy undergoing stereotactic electroencephalography (sEEG) monitoring participated in the study. Vibrotactile taVNS was administered across five vibration frequencies (2, 6, 12, 20, and 40 Hz) following a randomized stimulation pattern with 30 trials per frequency. Spectral coherence during stimulation was analyzed across theta (4–8 Hz), alpha (8–13 Hz), beta (13–30 Hz), and broadband gamma (70–170 Hz) frequency bands. At the group level, vibrotactile taVNS significantly increased coherence in theta (effect sizes 6 Hz: r = 0.311; 20 Hz: r = 0.316; 40 Hz: r = 0.264) and alpha bands (effect sizes 20 Hz: r = 0.455; 40 Hz: r = 0.402). Anatomically, multiple limbic brain regions exhibited increased coherence during taVNS compared to baseline. The percentage of total electrode pairs demonstrating increased coherence was also quantified at the individual level. Twenty Hz vibration resulted in the highest percentage of responder pairs across low-frequency coherence measures, with a group-average of 33% of electrode pairs responding, though inter-subject variability was present. Overall, vibrotactile taVNS induced significant low-frequency coherence increases involving several limbic system structures. Further, parametric characterization revealed the presence of inter-subject variability in terms of identifying the vibration frequency with the greatest coherence response. These findings encourage continued research into vibrotactile stimulation as an alternative modality for noninvasive vagus nerve stimulation.